Fungal endophyte association with Brachiaria grasses and its influence on plant water status, total non-structural carbohydrates and biomass production under drought stress - Odokonyero, Kennedy; Acuña, Tina Botwright; Cardoso Arango, Juan Andrés; Jiménez Serna, Juan de la Cruz; Rao, Idupulapati M. (Springer, 2016)
Aims: The main aim was to evaluate the effect of endophytic association of Sarocladium implicatum on drought responses of Brachiaria grass cultivars under greenhouse conditions. We tested the hypothesis that endophyte association with Brachiaria improves tolerance to drought stress by maintaining plant water status and increasing dry matter content (DMC), total nonstructural carbohydrate (NSC) contents and biomass. Methods: Five Brachiaria cultivars were grown in a greenhouse for 54 days, with (E+) and without (E-) endophyte under well-watered (WW) and droughts tressed (DS) conditions. Plant water status (measured as relative water content of leaf, RWC), leaf DMC, NSC contents and biomass were determined. Results: Endophyte association significantly increased leaf RWC but reduced DMC and biomass under DS. Endophyte reduced NSC contents under WW condition in one cultivar and reduced shoot, root and total biomass in another cultivar under DS. Effects of endophyte on response variables depended on cultivar and water regime, with significant interactions of these factors. Conclusions: Our results support the hypothesis that endophyte association improves plant water status by increasing RWC under DS. However, endophyte-induced reduction in plant attributes like DMC, NSC and biomass presents metabolic costs to host plants which could negatively affect forage quality and yield.